Prescription to practice in hypertension: a community experience in central Kerala - Mathew, Elsheba; Aiyappan, Rajalakshmy; M., Mili; N., Navaneetha; Shibu, Priyanka; Aravindakshan, Rajeev (International Journal of Research in Medical Sciences, 2017)
Background: Control of blood pressure is a global challenge and non-adherence to hypertension medications is a public health concern. Patient, medication and system related factors can contribute to non-adherence. The study was to determine adherence to hypertension medications and to understand the barriers to adherence in an adult group in Pathanamthitta District of Central Kerala. Methods: A cross sectional study was conducted in a community setting in 2016, among 139 adults aged 30 years and above on treatment for hypertension for at least six months. Those with gestational hypertension, those having serious comorbid conditions and those unwilling to participate were excluded. The data sheet included basic demographic information and history related to hypertension. A content validated eight item questionnaire was used to assess reported adherence and scores classified level of adherence as good (8), moderate (6-<8) and poor (<6). The data was analyzed using SPSS. Chi square test of significance and multivariate regression analysis were done. P<0.05 was considered statistically significant. Results: The participants were in the age group 34-91 years, 50.4% belonging to 50-69 years, and 75.5% were females. Adherence to hypertension medications was good in 49.6%, moderate in 31.7% and poor in 18.7%. The most common factors reported to contribute to non-adherence were forgetfulness (70.5%), high cost of medications (51.8%), and symptom-free state (27.3%). Conclusions: Adherence was good in less than half the study participants and poor in almost one-fifth. Forgetfulness and high medication costs were the most commonly reported barriers. These findings highlight the importance of individuals, families and health service, joining hands to tackle the public health problem of non-adherence to hypertension medications.